Student-teacher: resigning knowledge through the path and perception of the supervised curriculum internship (Research, Society and Development, 2021)
The Supervised Curricular Internship with the intention of producing knowledge takes into account the theory and trajectory of the student immersed in this praxis. This study was designed from the process of personal trajectory and academic training of the student in training, called an intern in pedagogical spaces and that we will call student-professor. This study aims to understand the academic and personal trajectory of the student-professor and their perception of the Supervised Internship in the Teacher Training Course for Early Childhood Education and Early Years in order to (re)signify knowledge and rethink teaching practices in initial training. This is a study with a qualitative approach with the participation of 7 students graduating from the Teacher Training Course of a public school in the interior of Rio Grande do Sul, with data collected between September and December 2020. The practice of the student- teacher in the formative path was felt with initial difficulties that gave rise to the construction of a solid practice recognized by these students. Resigning knowledge to this group of student-teachers is part of the reality of the Supervised Curricular Internship, where their experience and experience is built. It is on the school floor that knowledge and practices are shared and teaching knowledge takes place.